(untitled) (Ustozlar uchun, 2026)
In this article, we examine effective methods for developing spoken English skills in the modern educational environment. Particular attention is paid to the communicative approach, interactive teaching methods, and the use of digital technologies, including mobile apps, online platforms, and artificial intelligence systems. Methods such as pair and group language practice, role-playing, immersion, shadowing, and participation in conversation clubs are analyzed.